Covid19 Pandemic Crisis and its Reflection on the Pattern of University Education from the Perspective of the Teachers of College of Basic Education at University of Misan - fatima jaar Hussein ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
This study aims to reveal what the Covid19 pandemic crisis reflected on the pattern of university education from the perspective of the teachers of College of Basic Education at University of Misan .The researcher prepared a scale consisting of (10) paragraphs. After designing and presenting it to the experts and making the necessary adjustments to be in its final form and testing it on the exploratory sample that consisted of (20) teachers. After verifying its validity and reliability, the researcher applied it to the research sample, which numbered (40) teachers from the total research population of (120) teachers, which was chosen randomly using (SPSS)to extract the research results to know the average of each item included in the scale and the overall average of the total of the items.As well as calculating the difference between the averages. The results showed a positive indication, with a high agreement rate, on the impact of the Covid19 pandemic crisis on the pattern of education in terms of increasing knowledge of electronic skills and the way of their employment in education.As a result, the researcher concluded that there is a lack of interest in e-learning and its fundamentals before this crisis or to achieve what is called merged learning.Therefore, the researcher recommended making mastery of electronic skills or the basics of e-learning as a part of the teaching qualifications and requirements in university education as well as become part of annual performance evaluation.As well as providing appropriate training opportunities for faculty members on the use of computers and the internet and the use of various e-learning applications.